Location-specific growth and transfer of arrayed MoS2 monolayers with controllable size. (5th May 2017) - Wang, Xiaotian; Kang, Kyungnam; Chen, Siwei; Du, Ruozhou; Yang, Eui-Hyeok
Abstract: We present a controlled chemical vapor deposition (CVD) growth and transfer of arrayed MoS2 monolayers on predetermined locations. The patterned transition metal oxide (e.g. MoO3 ) source substrate was contacted face-to-face with an SiO2 growth substrate, where localized MoS2 flakes were synthesized on both source and growth substrates, following a CVD procedure. This growth technique enabled the growth of both single crystalline and polycrystalline MoS2 monolayer arrays with controlled size and location, exclusively on predetermined locations on the growth substrates. As-grown MoS2 arrays were transferred using a unique process that combines the wet and stamping transfer processes and dramatically enhanced the integrity of transferred MoS2 on microstructures, while protecting the microstructures during the transfer process. This fabrication technique can be applied to different transition metal dichalcogenides (TMDs) and allows the formation of TMDs on select locations, potentially eliminating a post-lithography step for device fabrication.